The Wiley Blackwell companion to medical sociology - Cockerham, William C. (Wiley Blackwell companions to sociology, 2021)
"The Wiley Blackwell Companion to Medical Sociology is a follow-up to two earlier volumes of this book and the latest work currently in Wiley Blackwell's Companion series. The goal is to bring together leading scholars in medical sociology to provide discussion of the most important issues and review the current research in the field. This edition follows this practice by providing chapters on health-related topics of significant interest. The contributors are from Canada, China, Singapore, Sweden, the United Kingdom, and the United States, who were carefully selected to write chapters on topics in which they were recognized experts. As will be seen in several chapters, this book was organized and written during the 2019-20 COVID-19 global pandemic. Consequently, many of these chapters take the effects of COVID-19 into account. One chapter (Chapter 21) on newly emerging diseases by Ron Barrett (Macalester College), a recipient of the Wellcome Medal from the Royal Anthropological Institute in the U.K., focuses directly on COVID-19 with an authoritative account of the pandemic. Part I of this volume begins with a chapter by Terrence Hill (Texas-San Antonio), myself, Jane McLeod (Indiana University), and Fred Hafferty (Mayo Clinic). It analyzes how medical sociology's former subfields of sociology in medicine and the sociology of medicine have changed as its subject matter has enlarged and expanded well beyond these two initial categories. Each of these co-authors addresses a particular area of contemporary research. Hill is one of the most prolific scholars in medical sociology, McLeod is Provost Professor and Chair of the Department of Sociology at Indiana University and recipient of both the James R. Greenley and Leonard I. Pearlin awards for distinguished contributions to the Sociology of Mental Health, and Hafferty is a past chair of the Medical Sociology Section of the American Sociological Association who is currently at the College of Medicine at Mayo Clinic in Rochester, Minnesota. He has spent his career as a sociologist working in medical institutions. Next, I join Graham Scambler (University College London and Surrey University, U.K.) to provide an overview of sociological theory in medical sociology. Scambler is a Fellow of the Academy of Social Sciences, U.K., and editor emeritus of the journal Social Theory & Health. Medical sociology's evolution from an applied and atheoretical field to a subdiscipline that not only draws from theory in sociology but contributes to it is noted. Current theories in the field are reviewed"--